Agricultural transformation in Sri Lanka: policy implications and way forward - Rao, P. Parthasarathy; Babu, Suresh Chandra; Weerahewa, Jeevika; Joshi, Pramod Kumar (International Food Policy Research Institute, 2017)
Sri Lanka continues to experience strong economic growth over the recent years. In the food and agriculture sector, however, there are several conspicuous policy changes that require attentive analysis. Also, since 2008, agriculture growth slowed down due to drought and weak global demand which affected exports and trade. This brief takes stock of key food and agricultural indicators and provides key recommendations to further expedite the transformation of the sector. Sri Lanka has come a long way in terms of agricultural transformation, moving from subsistence- based agrarian economy towards early integration stage. But further progress towards market- oriented industrialized agriculture will crucially depend on the policy, institutional, and technological innovations that are designed and implemented by the Government. The government of Sri Lanka has been pursuing large-scale reconstruction and development projects to achieve higher growth by developing small and medium enterprises and to increase agricultural productivity.